The Effect of Urban Expansion in Metro Manila on the Southwest Monsoon Rainfall - Dado, Julie Mae (Archīum Ateneo, 2019)
Model simulations of historical climate changes often do not take into account the climatic effects of changes in land use. Modifications in land cover such as urbanization, affect the partitioning of the water and energy balances, which in turn influences temperature and rainfall magnitudes and patterns. The local climate impacts of major urban expansion in metropolitan Manila (Metro Manila) in the Philippines is examined, particularly during the peak of the Southwest monsoon (SWM) rainfall season from July to September. MM5 is used to perform an ensemble simulation of experiments consisting of three-month runs for ten different years using two land cover scenarios representative of the urban cover of Metro Manila in 1972 and its expanded urban area in 2001. Results show that the SWM rainfall may be enhanced by up to 20% due to extensive urban growth. Comparison of model results with observation data indicates that without urban expansion, rainfall increases only by about 17%. When expanded urban impacts are included, the modeled increase in rainfall is about 29%, which is much closer to the observed value. This study therefore illustrates the significance of incorporating land use changes together with CO2 changes in climatic change modeling especially at the scale of local impacts.